Manajemen SDM Dalam Prespektif Ekonomi Islam Dengan Adanya Peranan IPTEK - Nur Fadilah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Islam is one of the religions embraced by the majority of Indonesia's population, which has given color to every aspect of its adherents' lives. Starting in terms of religion, politics, social and economics. The conventional economic view places worldliness alone, not yet looking at its spiritual needs. So employees are only the object of the company and are not subject to the company. With the application of Islamic Human Resource Management, employees will submit to the company so that they can actively participate for the company's progress. Manpower or Human Resources, is a factor of production that has a big meaning. Because all natural wealth is useless if it is not exploited by humans. Therefore every company should pay attention to HR as one of the factors of production. The Qur'an has given more attention to humans, this can be seen from the passage in the verse in the letter An Najm. (Afzalur Rahman, 1995), which means: "And that a human being has nothing but what he has tried" (An Najm: 39). It is reported in the verse that one way to get something out of the mini style is through hard work. The more earnest he works, the more wealth he will get. The principle is explained again in the letter An Nisaa., Through the word of Allah SWT, which means as follows: "For men there is a part of the business they do and for women there is also a part of the business they do." (An Nisaa: 32). The Islamic economic system in Indonesia implements human resource management, based on harmony or balancing the need for material and human ethics. The Islamic Economic System does not forget the main features of human progress, which is dependent on the extent of seamless and harmonious coordination between the moral and material aspects of human life.